Rapports organisation mondiale du commerce / Organisation pour l'harmonisation en Afrique du droit des affaires : contribution à l'étude du processus de mondialisation des rapports économiques et commerciaux. - Haidara, Hamzata (Université Nancy 2, 2009)
Le processus de mondialisation a modifié la configuration des relations internationales avec l'apparition de plusieurs organisations qui sont des moteurs de cette évolution. La mondialisation peut être définie comme un processus multidimensionnel caractérisé par une interdépendance dans tous les domaines et conduisant à une concurrence croissante. Elle est ainsi la manifestation du libéralisme international qui constitue à l'heure actuelle l'idéologie dominante. Elle véhicule un "sans frontièrisme" mettant fin au mythe du territoire en tant que cadre principal des relations internationales. Elle défie ainsi l'État en même temps qu'elle utilise son cadre territorial comme un moyen d'expression. L'OMC et l'OHADA sont les deux acteurs principaux de ce processus à des échelons différents : la première au niveau international, la seconde au niveau régional. Ces deux organisations sont-elles alors contradictoires ou bien complémentaires? En d'autres termes, pouvons-nous observer des interactions entre elles? Le principe de l'auto-affirmation de la supériorité traditionnelle du droit international ou universel leur est-il applicable? La concurrence pouvant intervenir entre elles conduit-elle à une cohabitation pacifique ou conflictuelle? Telles sont les questions auxquelles nous allons tenter de répondre. The process of globalization has led to the emergence of new players' international organizations- giving thus a new configuration to the international relations. Globalization can be defined as a multidimensional process characterized by the interdependence in all the areas and leading to an increasing competition. It is the manifestation of international liberalism which is currently the dominant ideology. This process implies the existence of a world without borders which ends the myth of the territory as the main framework of international relations. State is no longer considered as the major player on its own territory. Rather, new policies that include non state players are needed. The WTO and the OHADA are two main players in this process at different levels: the first at the international level, the second at the regional level. Are these two organizations contradictory or complementary? In other words, do they interact? Is the principle of self-assertion of the superiority of traditional international or universal law applicable to them? Does the competition that may occur between them lead to a peaceful or a conflicting coexistence? These are the main issues that the present study will try to tackle.
Keywords: Afrique; Droit communautaire; Droit des affaires; Mondialisation; Organisation mondiale du commerce; Organisation pour l'harmonisation en Afrique du droit des affaires; Organisations internationales; Organisations régionales; Souveraineté des Etats

Rethinking the world trade order: towards a better legal understanding of the role of regionalism in the multilateral trade regime - Abualethem Nsour, Mohammad Fahed (McGill University, 2009)
Regional Trade Agreements (RTAs) have proliferated at an unprecedented pace since the creation of the World Trade Organization (WTO). Although the WTO legally recognizes countries’ entitlement to form RTAs, neither the WTO nor parties to RTAs have an unequivocal understanding of the relationship between the WTO and RTAs. In other words, the legal controversies, the result of uncertainty regarding the application of the WTO/GATT laws, risk undermining the objectives of the multilateral trade system. This thesis tackles a phenomenon that is widely believed to be heavily economic and political. The thesis highlights the economic and political aspects of regionalism, but largely concentrates on the legal dimension of regionalism. The main argument of the thesis is that the first step to achieving harmony between multilateralism and regionalism is the identification of the legal uncertainties that regionalism produces when countries form RTAs without taking into account the substantive and procedural aspect of the applicable WTO/ GATT laws. The thesis calls for the creation of a legal instrument (i.e. agreement on RTAs) that combines all of the applicable law on RTAs, and simultaneously clarifies the legal language used therein. Likewise, the WTO should have a proactive role, not merely as a coordinator of RTAs, but as a watchdog for the multilateral system that has the power to prosecute violating RTAs. The author is aware that political concerns are top priorities for governments and policy makers when dealing with the regionalism problematic. Hence, legal solutions or proposals are not sufficient to create a better international trade system without the good will of the WTO Members who are, in fact, the players who are striving to craft more regional trade arrangements.
Keywords: GATT; International Trade; Regional Trade Agreements (RTAs); WTO

A balancing act: a framework for participation of non-state actors in the World Trade Organization - Majlessi, Mohammad (McGill University, 2009)
This thesis focuses on the interaction of two categories of non-state actors, private sector corporate actors and non-governmental organizations, with states in the context of the World Trade Organization (WTO) through a lens of public international law. It builds on the premise that the notion of states as the only subjects of international law is not adequate for a modern system of global governance, as it does not reflect the realities of fast-paced globalization and increased co-operation in a world where the boundaries of the private and public are increasingly blurred. It does not necessarily provide solutions for participation of non-state actors in the WTO, but demonstrates that developments in international relations warrant more space for participation of non-state actors, and that the current system of the WTO fails to provide sufficient space for participation. The thesis argues that, for both historical and pragmatic reasons, developments in the areas of GATT and international trade law occurred outside their natural course, leading to the myth of a “self-contained” trade regime not part of public international law. The WTO, unlike its predecessor, enjoys a proper institutional framework and mandate; one can no longer use the excuse of institutional handicap for excluding it from the system of global governance. Liberalization of international trade has far-reaching consequences which are not limited to the trade arena and the WTO, its member states, and scholars of international trade law have to assume their role in the broader context of an international legal order. Non-state actors’ formal participation can contribute to striking a balance between different forces and interests at work in the area of trade liberalization and its interplay with other non-trade issues. After setting the framework for the study, the thesis outlines modes of participation of non-state actors in the creation and modification of WTO law as well as in its enfor
Keywords: Balancing act; International Trade; WTO; World Trade Organization

Promouvoir la confiance dans le commerce électronique: questions juridiques relatives à l'utilisation internationale des méthodes d'authenification et de signature électroniques - United Nations Commission on International Trade Law (Publications des Nations Unies, 2009)
Keywords: Authentification; Commerce électronique; Signature électronique